Molecular pathogenesis and prevention of Staphylococcus aureus infections - Schneewind, Olaf (Henry Stewart Talks, 2009)
The envelope of gram-positive bacteria, Anchoring proteins, Signal peptides of staphylococcal surface proteins, Protein traffic to the cell wall envelope of S. aureus, Fate of S. aureus injected into mice bloodstream, Abscess formation, What are the protective antigens of staphylococci?, Surface proteins and protective immunity, Staphylococcal abscesses enable persistence, Protein topologies in the cell wall of staphylococci, Vaccine protection against lethal challenge, S. aureus and human lung infections, Active/passive immunization